Methods of Translating Names of Material Culture Objects into Russian (Translation of Yuan Ke’s “Myths of Ancient China”) - Junling Gu; Xiaoyu Zhang; Yu. V. Pogrebnyak (Научный диалог)
This article analyzes the existing translation of Yuan Ke’s “Myths of Ancient China” (1960), carried out by E. I. Lubo-Lesnichenko and E. V. Puzitsky (1965), focusing on the strategies employed by the translators in conveying Chinese names into Russian in instances of cultural gaps. The aim of the article is to summarize the strategies adhered to by the authors in translating Chinese mythological narratives and to identify the most suitable methods for rendering names of material culture objects into Russian. An assessment is provided regarding the accuracy of translations of fragments of myths that mention concepts such as “tripod,” “jade hairpin,” “jade tablet,” “Jai-gong, Palace of Abstinence,” and others. The analysis reveals that the methods utilized by translators of ancient Chinese myths primarily include phonetic transliteration, literal translation, addition, omission, and annotation. However, the application of these strategies sometimes results in distortion and omission of the original information. This article proposes translational strategies, within the framework of foreignization, that should be adhered to when translating Chinese mythological narratives: addition, omission, transfer, substitution, division, combination, and transliteration.